Political connection heterogeneity and firm value in Vietnam - Phuoc Vu Ha; Michael Frömmel (Cogent Business & Management, 2020)
The observation of firms' political connections (PCs) in both types of ascribed and acquired PCs has raised the question of their benefits to firms' operation. Based on 1,365 Vietnamese listed firm-year observations from 2010 to 2014, we find that although firms with both ascribed and acquired PCs have lower firm value (FV) than firms without any PCs, firms with acquired PCs exhibit better FV than those with ascribed PCs. The paper also reveals that concentrated ownership (CO) has a mediation impact on the association between acquired PCs and FV while it can help firms with acquired PCs in improving FV.
Keywords: G32; G38; O16; O53; 650; political connections; concentrated ownership; firm value